2005
DOI: 10.1186/1471-2202-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundMechanisms that affect recovery from fetal and neonatal hypoxic-ischemic (H-I) brain injury have not been fully elucidated. The incidence of intrapartum asphyxia is approximately 2.5%, but the occurrence of adverse clinical outcome is much lower. One of the factors which may account for this relatively good outcome is the process of neurogenesis, which has been described in adult animals. We used a neonatal mouse model to assess new cells in the hippocampus after H-I injury.ResultsNeonatal mice under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 32 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Indeed, increased neurogenesis has been observed in brain regions affected by HI [120, 214, 217, 218], including DG, CA1 [43, 213, 219, 220], subventricular zone (SVZ) [221, 222], neostriatum [223] and neocortex [224, 225]. It has been suggested that new cells produced in SVZ can migrate to the lesioned regions [226229], attracted by stromal cell-derived migratory signalling.…”
Section: Perinatal Asphyxia and Neurogenesis: Endogenous Brain Rescuementioning
confidence: 99%
“…Indeed, increased neurogenesis has been observed in brain regions affected by HI [120, 214, 217, 218], including DG, CA1 [43, 213, 219, 220], subventricular zone (SVZ) [221, 222], neostriatum [223] and neocortex [224, 225]. It has been suggested that new cells produced in SVZ can migrate to the lesioned regions [226229], attracted by stromal cell-derived migratory signalling.…”
Section: Perinatal Asphyxia and Neurogenesis: Endogenous Brain Rescuementioning
confidence: 99%
“…Adult hippocampal neurogenesis is responsible for generating new neurons in the brain and found to be triggered by brain injuries and stress including hypoxia to replace damaged and malfunctioned neurons [ 20 , 21 ]. Neurogenic BrdU-labeled and proliferative PCNA-labeled cells were increased in the mice hippocampus and primary hippocampal cultures following hypoxia or ischemia-induced hippocampal apoptosis, which may involve MAP kinase signaling pathway [ 22 , 23 ]. Also, administration of hydrogen sulfide could restore hypoxia-induced cognitive impairment of mice by enhancing hypoxia-triggered hippocampal neurogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus has been the subject of several types of research using different models of oxygen deprivation due to its susceptibility to insults [25]. Post-mortem analysis showed that the damage was almost entirely limited to the CA1 subfield of the hippocampus [26], whereas CA2 and CA3 subfields appear to be more resistant to ischaemic events [27,28].…”
Section: Discussionmentioning
confidence: 99%